2017
DOI: 10.1080/2162402x.2017.1288330
|View full text |Cite
|
Sign up to set email alerts
|

Digital analysis and epigenetic regulation of the signature of rejection in colorectal cancer

Abstract: The immune system plays a pivotal role in the development and progression of colorectal cancer (CRC). Tumor immune rejection has been previously linked to the activation of the interferon-stimulated genes (ISG) STAT1, IRF-5 and IRF-1. Specific immunoregulatory microRNAs (miRNAs) may impact the expression of these ISG in the tumor microenvironment. In this translational study, we develop a digital image analysis protocol to identify the ISG-gene expression signature and investigate miRNA expression in the immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Virtual multistaining also offers the unique opportunity of combining distinct histological methods, such as RNA in situ hybridization and IHC for multiparametric tissue profiling. This approach has been recently used to spatially correlate the expression of specific microRNAs, interferon-stimulated target genes, T cell infiltration, and the expression of cytotoxic effector molecules in the microenvironment of CRC [ 45 ]. Limitations include the requirement for multiple tissue sections, inevitable sectioning artifacts, and the need to perform complex image transformation procedures for precise image alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Virtual multistaining also offers the unique opportunity of combining distinct histological methods, such as RNA in situ hybridization and IHC for multiparametric tissue profiling. This approach has been recently used to spatially correlate the expression of specific microRNAs, interferon-stimulated target genes, T cell infiltration, and the expression of cytotoxic effector molecules in the microenvironment of CRC [ 45 ]. Limitations include the requirement for multiple tissue sections, inevitable sectioning artifacts, and the need to perform complex image transformation procedures for precise image alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Granzyme B ( GZMB ) (HR = 0.742, P < 0.001), whose encoded preproprotein is secreted by natural killer cells and cytotoxic T-lymphocytes, also acted as an independent protective factor for the prognosis of patients with CRC. Koelzer et al (2017) found that the immune-activated phenotype was associated with high counts of intratumoral CD8 cytotoxic T-lymphocytes ( P = 0.007) and the expression of the immune effector molecule GZMB ( P < 0.001). The increased infiltration of cytotoxic T-lymphocytes is the key to tumor immune rejection.…”
Section: Discussionmentioning
confidence: 98%
“…A previous study demonstrates that the PD-L1 status in the tumor is a biomarker that reflects the response or resistance to ICIs, which was consistent with our conclusion ( 66 ). Furthermore, some comprehensive studies have revealed a mechanistically meaningful role of targeting TME, evidenced by the positive association of the ‘T-cell-inflamed tumor microenvironment’ with the effectiveness of diverse immune treatment ( 67 69 ).…”
Section: Discussionmentioning
confidence: 99%